2016
DOI: 10.7883/yoken.jjid.2015.519
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of LAMP-TB Method for Diagnosing Tuberculosis in Haiti

Abstract: SUMMARY:The procedure of ultra-rapid extraction (PURE) and loop-mediated isothermal amplification for tuberculosis (LAMP-TB) is a simple and rapid manual tuberculosis diagnostic with mediumthroughput capability. Because of its simplicity, this method could be useful in resource-limited conditions such as microscopy centers in developing countries. This study was conducted to evaluate the clinical performance of this method in a point-of-care setting. The performance was compared to that of smear microscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…There are several published reports on the diagnostic potential of LAMP assays for TB diagnosis. The overall performance varied greatly across the studies (5, [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…There are several published reports on the diagnostic potential of LAMP assays for TB diagnosis. The overall performance varied greatly across the studies (5, [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The LAMP technique has been adapted for use in the diagnosis of different infectious diseases with notoriously high burdens, including tuberculosis and malaria, for which high sensitivity, specificity, affordability, and applicability to the tropical field are desired [ 24 ]. Among the advantages of this kit compared to PCR are that it requires less investment, staff training, and operating time.…”
Section: Discussionmentioning
confidence: 99%
“…Several evaluation studies have been conducted in various countries. However, the performance indicators varied greatly across the studies [ 10 11 12 13 ]. Previous studies have shown that TB-LAMP has lower sensitivity than fluorescence microscopy (FM) and that the performance of TB-LAMP is insufficient in smear-negative samples [ 14 15 ].…”
Section: Discussionmentioning
confidence: 99%